ANALISIS STRUKTUR VERTIKAL MJO TERKAIT DENGAN AKTIVITAS SUPER CLOUD CLUSTERS (SCCs) DI KAWASAN BARAT INDONESIA - Eddy Hermawan (Lembaga Penerbangan dan Antariksa Nasional, 2010)
One important aspect when its Coupling Processes Equatorial Atmosphere (CPEA) Campaign 2004 in Kototabang which lasted for approximately one month of observation (April 10 to May 10, 2004) was an analysis of the vertical structure of the phenomenon of the Madden-Julian Oscillation (MJO) related to the activity of the Super Cloud Clusters (SCCs) as one of the main parameters in assessing the behavior of rainfall occurred in the western region of Indonesia. The data used are data of Equatorial Atmosphere Radar (EAR), Boundary Layer Radar (BLR), Mini Automatic Weather Station (MAWS), and Optical Rain Gauge (ORG) at Kototabang, LAPAN Ground Station. While the supporting data used are long-wave radiation anomaly data (Outgoing Longwave Radiation, OLR) and surface rainfall data. The analysis using spectral techniques, particularly the Fast Fourier Transform (FFT) on data anomalies daily average five (pentad) OLR oscillation 2001-2005 period shows that the dominant than the data is approximately 30 daily. These oscillations typically occurred in the lower troposphere layer with the direction of propagation toward the east. Besides that, the existence of convergence and divergence processes in the layer 3 and 10 km above mean sea level (msl) is also found, particularly on the date April 23, 2004 of EAR data analysis. Finally, we try to link these events by analyzing the relationship between OLR with the rainfall in Kototabang and the surrounding region, particularly ORG measurement results with the correlation coefficient of about 0.71. Keywords : CPEA Campaign, MJO, OLR, EAR, and ORG